Large Ln42 coordination nanorings: NIR luminescence sensing of metal ions and nitro explosives. Issue 87 (16th October 2019) - Shi, Dongliang; Yang, Xiaoping; Chen, Hongfen; Jiang, Dongmei; Liu, Jieni; Ma, Yanan; Schipper, Desmond; Jones, Richard A.
Abstract : Two 42-metal lanthanide nanorings [Ln42 L14 (OH)28 (OAc)84 ] (Ln = Nd (1 ), La (2 )) were constructed, and the Nd42 cluster exhibits NIR luminescent sensing of metal cations and nitro explosives. Abstract : Two 42-metal lanthanide coordination nanorings [Ln42 L14 (OH)28 (OAc)84 ] (Ln = Nd (1 ), La (2 )) were prepared using a vanillin type ligand. The Nd42 cluster exhibits interesting NIR luminescence sensing behavior to metal ions and nitro explosives.